A Normative Study of Generative Artificial Intelligence in Higher Education and Implications - Ji, Mingyang; Liu, Yue (LPPM STIKI Malang, 2024)
Generative Artificial Intelligence (AI) has been developing rapidly and its application in higher education is becoming more and more widespread. The action research project of generative AI application by teachers in Tianhe District, Guangzhou City and the application case of Chat Generative Pre-trained Transformer are selected to illustrate that generative AI has brought unprecedented changes to many aspects of education and teaching, academic research, student management and services, and intelligent campus construction. However, along with these extensive applications, a series of ethical risk issues have gradually come to the fore. According to existing research, four major ethical risks of generative AI have been proposed: technology ontology risk, educational data risk, machine algorithm risk, and educational application risk. Combined with the literature